Foreign Direct Investment and Growth in ECOWAS: An ARDL Panel Analysis - (:unkn) unknown (My University, 2024)
This study examines the impact of core macroeconomic indicators on growth across Sixteen (16) West African countries using the Pooled Mean Group (PMG) estimation technique within a Panel ARDL framework. The analysis covers variables such as Foreign Direct Investment (FDI), Gross Capital Formation, percentage of working population growth, access to electricity, and inflation. The findings reveal that the effects of FDI on growth were mixed. While FDI positively impacts real GDP growth in some countries such as Benin, Cabo Verde, and Mauritania, its effect was however, negative in others such as Nigeria and Gambia. Gross capital formation, on the other hand, consistently supports short-run growth across most countries, while inflation emerges as a destabilizing factor. The speed of adjustment toward long-run equilibrium varies significantly, with countries such as Guinea-Bissau and Nigeria correcting economic shocks faster than others. This study contributes to the literature on economic growth dynamics in Africa by showing the heterogeneous responses of these countries to similar macroeconomic factors. It validates the need for country-specific policies that focus on stabilizing inflation, optimizing domestic investment, and effectively leveraging foreign direct investment. Also, improvements in infrastructure and access to markets are crucial for facilitating long-term growth across the region. The study provides valuable insights for policymakers and stakeholders aiming to achieve sustainable growth in the ECOWAS region.
Keywords: African Research